Effect of Organizational Culture, Organizational Communication, Quality Work of Life and Work Environment on Employee Performance for Regional Secretariat Employees in Bandung City Government Environment - Shinta Oktafien; Wahyu Wibisono; Deni Darmawan; Stefanus M S Sadana; Andreas Wahyu Gunawan P (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to describe how organizational culture, organizational communication, quality of work of life, work environment, and employee performance of the Regional Secretariat in Bandung City Government are, along with their influence among the variables studied. The population in this study were all employees who worked at the Regional Secretariat in the Bandung City Government, totaling 261 people. The number of samples taken in this study, namely 261 employees as much as the total population with saturated sampling technique or census. Determination of the sample in this study was carried out with the type of Non-Probability Sampling. Non-Probability Sampling This type of sample is not chosen at random. The selected non-probability sampling technique is saturated sampling (census), which is a sampling method when all members of the population are used as samples. Meanwhile, the research method used in this study is in the form of an explanatory survey research method which aims to find out the relationship between the variables studied. The data analysis and processing technique used is in the form of path analysis. Based on the research results, it is known that organizational culture, organizational communication, and work environment, either directly or indirectly, have a significant influence on employee performance of the Regional Secretariat in the Bandung City Government. However, in this study, the quality of work of life did not have a significant effect on employee performance.